2020
DOI: 10.1002/hyp.13986
|View full text |Cite
|
Sign up to set email alerts
|

A δ18O and δ2H stable water isotope analysis of subalpine forest water sources under seasonal and hydrological stress in the Canadian Rocky Mountains

Abstract: Subalpine forests are hydrologically important to the function and health of mountain basins. Identifying the specific water sources and the proportions used by subalpine forests is necessary to understand potential impacts to these forests under a changing climate. The recent "Two Water Worlds" hypothesis suggests that trees can favour tightly bound soil water instead of readily available free-flowing soil water. Little is known about the specific sources of water used by subalpine trees Abies lasiocarpa (Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…Second, the soil depths of these two aspects were different. The root structure of subalpine forest species is affected by bedrock, limiting the root depth (Langs et al, 2020; Liu et al, 2011). In the study area, soil depth until the bedrock was greater on the semi‐sunny aspect (0–80 cm) than on the semi‐shaded aspect (0–60 cm); thus, the roots of subalpine shrubs could reach deeper soil to absorb soil water on the semi‐sunny aspect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the soil depths of these two aspects were different. The root structure of subalpine forest species is affected by bedrock, limiting the root depth (Langs et al, 2020; Liu et al, 2011). In the study area, soil depth until the bedrock was greater on the semi‐sunny aspect (0–80 cm) than on the semi‐shaded aspect (0–60 cm); thus, the roots of subalpine shrubs could reach deeper soil to absorb soil water on the semi‐sunny aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Langs et al (2020) found differences in the water sources of subalpine forests under seasonal and hydrological pressures in the Canadian Rockies, and emphasized the importance of soil moisture reserves for the health of subalpine forests. Consistent with Langs' findings, our study found that soil water is essential for the growth and development of subalpine shrubs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The macropore findings of the study by (Renée Brooks et al, 2010) have been confirmed to some extent in many biomes across the globe (Evaristo et al, 2016; Javaux et al, 2016). Other studies revealed that under a rainy temperate (Herve‐Fernandez et al, 2016), humid subtropical (Luo et al, 2019), tropical savanna (Mahindawansha et al, 2020) or subalpine (Langs et al, 2020) climate these interactions may be seasonally limited and dependent on soil moisture conditions. Bowling et al (2017) examined whether snowmelt water can create a unique pool of tightly bound water that is used by plants in seasonally snow‐covered areas during the growing season.…”
Section: Introductionmentioning
confidence: 99%